Residual Bioprosthetic Valve Immunogenicity: Forgotten, Not Lost - Human, Paul; Bezuidenhout, Deon; Aikawa, Elena; Zilla, Peter (Frontiers in Cardiovascular Medicine, 2022)
Despite early realization of the need to control inherent immunogenicity of bioprosthetic replacement heart valves and thereby mitigate the ensuing host response and its associated pathology, including dystrophic calcification, the problem remains unresolved to this day. Concerns over mechanical stiffness associated with prerequisite high cross-link density to effect abrogation of this response, together with the insinuated role of leaching glutaraldehyde monomer in subsequent dystrophic mineralization, have understandably introduced compromises. These have become so entrenched as a benchmark standard that residual immunogenicity of the extracellular matrix has seemingly been relegated to a very subordinate role. Instead, focus has shifted toward the removal of cellular compartment antigens renowned for their implication in the failure of vascularized organ xenotransplants. While decellularization certainly offers advantages, this review aims to refocus attention on the unresolved matter of the host response to the extracellular matrix. Furthermore, by implicating remnant immune and inflammatory processes to bioprosthetic valve pathology, including pannus overgrowth and mineralization, the validity of a preeminent focus on decellularization, in the context of inefficient antigen and possible residual microbial remnant removal, is questioned.